Pengaruh Covid-19, Tingkat Inflasi dan Harga Minyak Mentah Terhadap Keputusan Investasi di Bursa Efek Indonesia - Nyimas Lutfiyah (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
Macroeconomic conditions will affect the capital market and will certainly affect investors in predicting future economic changes. The purpose of this study is to determine the effect of Covid-19, inflation rates and oil prices on investment decisions on the Indonesia Stock Exchange. The sample in this study is the number of confirmed cases of Covid-19, inflation rate and oil prices for the period March 2020 - January 2022. This type of research is associative research. The data used in this study is time-series data. Methods of data collection using the method of documentation. The data analysis method used is quantitative. The data analysis technique used multiple linear regression. The results showed that (1) Covid-19 had a significant effect on stock prices and trading volume, (2) Inflation rates had no significant effect on stock prices and trading volume, (3) Crude oil prices had a significant effect on stock prices and trading volume